Sustainable Development Strategy in the Bali Green School Area - Agustin, Selvia Noer; Acwin Dwijendra, Ngakan Ketut (ASTONJADRO, 2023)
Sustainable development is development to meet the needs of the present generation without compromising the ability of future generations to meet their needs in terms of environmental, economic and social aspects. Green School Bali, one of the educational areas in Bali that implements sustainable development. This study aims to determine the sustainable development strategy applied in the Bali Green School area. To assess whether an area is implementing sustainable development or not, an indicator is needed, which in this study uses GREENSHIP Regions. In this indicator there are seven categories and are grouped into sub-indicators which are further elaborated. This study will record whether these indicators are applied or not in reality through literature review, direct observation and interviews. So it can be concluded that the Bali Green School area implements a sustainable development strategy according to the GREENSHIP Area indicators.